Uncovering the temporal dynamics and regulatory networks of thermal stress response in a hyperthermophile using transcriptomics and proteomics - Felix Grünberger; Georg Schmid; Zubeir El Ahmad; Martin Fenk; Katharina Vogl; Robert Reichelt; Winfried Hausner; Henning Urlaub; Christof Lenz; Dina Grohmann (mBio, 2023)
ABSTRACTFacing rapid fluctuations in their natural environment, extremophiles, like the hyperthermophilic archaeon Pyrococcus furiosus, exhibit remarkable adaptability to extreme conditions. However, our understanding of their dynamic cellular responses remains limited. This study integrates RNA-sequencing and mass spectrometry data, thereby elucidating transcriptomic and proteomic responses to heat and cold shock stress in P. furiosus. Our results reveal rapid and dynamic changes in gene and protein expression following these stress responses. Heat shock triggers extensive transcriptome reprogramming, orchestrated by the transcriptional regulator Phr, targeting a broader gene repertoire than previously demonstrated. For heat shock signature genes, RNA levels swiftly return to baseline upon recovery, while protein levels remain persistently upregulated, reflecting a rapid but sustained response. Intriguingly, cold shock at 4°C elicits distinct short- and long-term responses at both RNA and protein levels. Cluster analysis identified gene sets with either congruent or contrasting trends in RNA and protein changes, representing well-separated arCOG groups tailored to their individual cellular responses. Particularly, upregulation of ribosomal proteins and significant enrichment of 5′-leadered sequences in cold-shock responsive genes suggest that translation regulation is important during cold shock adaption. Further investigating transcriptomic features, we reveal that thermal stress genes are equipped with basal sequence elements, such as strong promoter and poly(U)-terminators, facilitating a regulated response of the respective transcription units. Our study provides a comprehensive overview of the cellular response to temperature stress, advancing our understanding of stress response mechanisms in hyperthermophilic archaea and providing valuable insights into the molecular adaptations that facilitate life in extreme environments.IMPORTANCEExtreme environments provide unique challenges for life, and the study of extremophiles can shed light on the mechanisms of adaptation to such conditions. Pyrococcus furiosus, a hyperthermophilic archaeon, is a model organism for studying thermal stress response mechanisms. In this study, we used an integrated analysis of RNA-sequencing and mass spectrometry data to investigate the transcriptomic and proteomic responses of P. furiosus to heat and cold shock stress and recovery. Our results reveal the rapid and dynamic changes in gene and protein expression patterns associated with these stress responses, as well as the coordinated regulation of different gene sets in response to different stressors. These findings provide valuable insights into the molecular adaptations that facilitate life in extreme environments and advance our understanding of stress response mechanisms in hyperthermophilic archaea.